The walking dead and killing state: Zombification and the normalization of police violence. (November 2014) - Linnemann, Travis; Wall, Tyler; Green, Edward
In May 2012, police shot Rudy Eugene, a black man of Haitian decent, dead as he 'ate the face' of a homeless man on a deserted Miami causeway. Because of the strange gruesomeness of the attack and other similar violent acts, some in the media declared that a terrifying pandemic—the 'zombie apocalypse'—had arrived. While this particular case may be yet another instance of mediated panic, we suggest cries of 'zombies' and 'cannibals' should not be dismissed as simply sensationalistic, irresponsible journalism. Rather, we see this case as a powerful example of the cultural production of a spectral sort of monstrosity that obscures and justifies police violence and state killing. As such, we argue that all of the contemporary 'zombie talk', usefully reveals how the logics of security, state violence and punitive disposability are imagined and reproduced as livable parts of late-capitalism.